Design of Multijunction Photovoltaic Cells Optimized for Varied Atmospheric Conditions - C. Zhang; J. Gwamuri; R. Andrews; J. M. Pearce (International Journal of Photoenergy)
Band gap engineering provides an opportunity to not only provide higher overall conversion efficiencies of the reference AM1.5 spectra but also customize PV device design for specific geographic locations and microenvironments based on atmospheric conditions characteristic to that particular location. Indium gallium nitride and other PV materials offer the opportunity for limited bandgap engineering to match spectra. The effects of atmospheric conditions such as aerosols, cloud cover, water vapor, and air mass have been shown to cause variations in spectral radiance that alters PV system performance due to both overrating and underrating. Designing PV devices optimized for spectral radiance of a particular region can result in improved PV system performance. This paper presents a new method for designing geographically optimized PV cells with using a numerical model for bandgap optimization. The geographic microclimate spectrally resolved solar flux for twelve representative atmospheric conditions for the incident radiation angle (zenith angle) of 48.1° and fixed array angle of 40° is used to iteratively optimize the band gap for tandem, triple, and quad-layer of InGaN-based multijunction cells. The results of this method are illustrated for the case study of solar farms in the New York region and discussed.